Uniportal Robotic-Assisted Tracheal Resection and Reconstruction Under Spontaneous Ventilation - Ricardo Eli Guido Guerra; Francina Valezka Bolaños Morales; Oscar Francisco Silva Gómez; Hector Olvera Prado; Sarahí Ibáñez Barzalobre; Mugurel Bosinceanu; Diego Gonzalez-Rivas (Case Reports in Anesthesiology)
Conclusions: Nonintubated uniportal robotically assisted tracheal resection and reconstruction is a feasible, less invasive technique that offers significant benefits in terms of recovery and patient comfort when performed by experienced surgeons.